2022
DOI: 10.3390/biom12081155
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Effects of Ultramicronized Palmitoylethanolamide in the Management of Neuropathic Pain and Associated Mood Disorders Induced by Paclitaxel in Mice

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common complication of antineoplastic drugs, particularly paclitaxel (PTX). It can affect the quality of patients’ lives and increase the risk of developing mood disorders. Although several drugs are recommended, they yielded inconclusive results in clinical trials. The aim of the present work is to investigate whether the palmitoylethanolamide (PEA) would reduce PTX-induced CIPN and associated mood disorders. Moreover, the role PPAR-α and the endocannabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these therapies exhibited moderate efficacy and significant side effects such as somnolence, constipation, tolerance, and dizziness [ 60 ]. In addition, some treatments only improved neuropathy or one of the emotional disorders associated with chemotherapy-induced neuropathic pain [ 61 , 62 , 63 ], but only a few studies evaluated the possible effects of different treatments in the management of PIPN-associated mood disorders [ 13 , 64 , 65 ]. In this line, this study demonstrated that treatment with HRW inhibited neuropathy and avoided the cognitive and emotional deficits associated.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Furthermore, as many other neuropathic conditions, neuroinflammation and microglial phenotypic change are fundamental mechanisms in the pathogenesis of CIPN. 19 , 20 PEA modulates the cannabinoid receptors 2 (CB2) expression and potentiates the activity of other endocannabinoid mediators, and its role as a preventive or therapeutic has been demonstrated in animal models of CIPN induced by oxaliplatin and taxanes. 20–22 Furthermore, in a small clinical study, PEA administration to patients affected by painful CIPN has shown a beneficial effect on myelinated nerve fibers function and pain.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 PEA modulates the cannabinoid receptors 2 (CB2) expression and potentiates the activity of other endocannabinoid mediators, and its role as a preventive or therapeutic has been demonstrated in animal models of CIPN induced by oxaliplatin and taxanes. 20–22 Furthermore, in a small clinical study, PEA administration to patients affected by painful CIPN has shown a beneficial effect on myelinated nerve fibers function and pain. 23 As confirmed by the results of this survey, most respondents consider PEA as a first line agent for CIPN management, despite no robust evidence is available and this nutraceutical is not mentioned in CIPN guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known anti-inflammatory and antinociceptive effects of PEA (palmitoylethanolamide) are considered a beneficial strategy in the management of the oxaliplatin- [148] and paclitaxel- [149] induced CIPN model, as well as in osteoarthritis [150] and fibromyalgia studies [151]. Cristiano et al, 2022 demonstrated that um-PEA (ultramicronized PEA) reduced the development of hypersensitivity with an effect associated with the reduction of spinal cord and hippocampal proinflammatory cytokines, as well as antidepressant and anxiolytic effects [152].…”
Section: Treatment Strategiesmentioning
confidence: 99%